Beyond the gats: Implicit engines in services RTAs - Daniltsev Alexander (Panoeconomicus, 2015)
In the last 15 years the reciprocity of regional trade agreements on services has become a global phenomenon. Whereas main provisions regulating access to the services market are fixed by specific obligations under the General Agreement on Trade in Services, RTAs have been considered a flexible means for liberalization and an expedient to protect national service providers. This article explores the role of the GATS and other agreements, both under and not under the mandate of the World Trade Organization, in trade blocs. The econometric model developed by the authors shows that the removal of restrictions for foreign suppliers under domestic regulation (consumer protection, regulation of labor market) and the elimination of discriminatory measures on foreign investments that affect trade in goods are likely to be more important for the expansion of services trade on a preferential basis than the GATS-type liberalization.